Optimization of Health Workers in The Implementation of Provider Initiated HIV Testing and Counseling (PITC) - Hikmah, Faiqatul; Fernandes, Angelina da Costa; Karimah, Rinda Nurul; Suandana, Iwan Abdi; Susindra, Yoswenita (Indonesian Journal Publisher, 2024)
Background: Provider Initiated HIV Testing and Counseling (PITC) is a service offering HIV testing by health workers to all patients in health facilities1. The quality of PITC services that do not meet standards is still a problem, thus becoming an obstacle to PITC services. This causes PITC user satisfaction to be low. The aim of this research is to determine efforts to optimize health workers in the implementation of provider-initiated HIV testing and counseling (PITC). This systematic research was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method to assess, review and synthesize research. Search through the database by entering the keywords